Effect of menstrual cycle phase on physiological responses in healthy women at rest and during submaximal exercise at high altitude - Guia Tagliapietra; Tom Citherlet; Antoine Raberin; Nicolas Bourdillon; Bastien Krumm; Benjamin J. Narang; Guido Giardini; Vincent Pialoux; Tadej Debevec; Grégoire P. Millet (Scientific Reports)
Abstract As more women engage in high-altitude activities, understanding how ovarian hormone fluctuations affect their cardiorespiratory system is essential for optimizing acclimatization to these environments. This study investigates the effects of menstrual cycle (MC) phases on physiological responses at rest, during and after submaximal exercise, at high-altitude (barometric pressure 509 ± 6 mmHg; partial pressure of inspired oxygen 96 ± 1 mmHg; ambient temperature 21 ± 2 °C and relative humidity 27 ± 4%) in 16 eumenorrheic women. Gas exchange, hemodynamic responses, heart rate variability and heart rate recovery (HRR) were monitored at low altitude, and then at 3375 m on the Mont Blanc (following nocturnal exposure) during both the early-follicular (EF) and mid-luteal (ML) phases. Significant differences were observed between low and high-altitude in ventilation, heart rate and cardiac output. Resting ventilation (15.2 ± 1.9 vs. 13.2 ± 2.5 L.min-1; p = 0.039) and tidal volume (812 ± 217 vs. 713 ± 190 mL; p = 0.027) were higher during EF than ML at high-altitude. These differences between EF and ML were no longer evident during exercise, with comparable responses in oxygen uptake kinetics, cycling efficiency and HRR. The MC had negligible effects on physiological responses to high-altitude. An individualized approach, tailored to each woman’s specific responses to hypoxia across the MC, may be more beneficial in optimizing high-altitude sojourns than general guidelines.